CMIP6 projects less frequent seasonal soil moisture droughts over China in response to different warming levels - Sisi Chen; Xing Yuan (Environmental Research Letters, 2021)
Seasonal drought occurrences are found to increase across different regions over China under global warming, but with large uncertainties among models. With ten selected Coupled Model Intercomparison Project Phase 5 (CMIP5) climate models and seven CMIP6 models according to their performances in reproducing historical drought trends ( p < 0.1), here we show that future seasonal soil moisture (SM) droughts over China projected by CMIP6 models are less frequent than that by CMIP5 models. We find national mean seasonal drought frequency is projected to increase by 28 ± 4% based on CMIP5 models at 1.5 °C global warming level, but only increase by 18 ± 6% based on CMIP6 models and 12 ± 4% based on land surface model ensemble simulations driven by downscaled CMIP5 models. Compared with CMIP6, CMIP5 projection suggests larger increase in precipitation but also larger increase in evapotranspiration, leading to more frequent seasonal SM droughts. Comparing the results at 3 °C global warming level with those at 1.5 °C, drought frequency over China will increase further by 10 ± 4%, but drought duration will decrease by 6 ± 4%, suggesting more frequent seasonal SM droughts with shorter durations will occur in a warming future. The future increase in China drought frequency will reduce from 12%–45% based on selected climate models to 3%–27% based on all available models (30 CMIP5 models and 31 CMIP6 models), which indicates that the model selection is critical for future drought projection. Nevertheless, CMIP6 still projects less frequent seasonal SM droughts than CMIP5 even without any model discriminations.